A Large Outbreak of Hepatitis C Virus Infections in a Hemodialysis Clinic. (17th November 2015) - Nguyen, Duc B.; Gutowski, Jennifer; Ghiselli, Margherita; Cheng, Tabitha; Bel Hamdounia, Shadia; Suryaprasad, Anil; Xu, Fujie; Moulton-Meissner, Heather; Hayden, Tonya; Forbi, Joseph C.; Xia, Guo-liang; Arduino, Matthew J.; et al.
Abstract : BACKGROUND: In November and December 2012, 6 patients at a hemodialysis clinic were given a diagnosis of new hepatitis C virus (HCV) infection. OBJECTIVE: To investigate the outbreak to identify risk factors for transmission. METHODS: A case patient was defined as a patient who was HCV-antibody negative on clinic admission but subsequently was found to be HCV-antibody positive from January 1, 2008, through April 30, 2013. Patient charts were reviewed to identify and describe case patients. The hypervariable region 1 of HCV from infected patients was tested to assess viral genetic relatedness. Infection control practices were evaluated via observations. A forensic chemiluminescent agent was used to identify blood contamination on environmental surfaces after cleaning. RESULTS: Eighteen case patients were identified at the clinic from January 1, 2008, through April 30, 2013, resulting in an estimated 16.7% attack rate. Analysis of HCV quasispecies identified 4 separate clusters of transmission involving 11 case patients. The case patients and previously infected patients in each cluster were treated in neighboring dialysis stations during the same shift, or at the same dialysis station on 2 consecutive shifts. Lapses in infection control were identified. Visible and invisible blood was identified on multiple surfaces at the clinic. CONCLUSIONS: Epidemiologic and laboratory data confirmed transmission of HCV among numerous patients at the dialysis clinic over 6 years. Infection control breaches were likely responsible. This outbreak highlights the importance of rigorous adherence to recommended infection control practices in dialysis settings. Infect. Control Hosp. Epidemiol. 2016;37(2):125–133